A methodology for analysing human movement patterns and performance using acceleration time series - Ohgi, Y.; Mokuno, T.; Yamagishi, M.; Miyaji, C. (The Engineering of sport, 1998)
Untersucht wurde die Beschleunigung des Handgelenks während einer Schlagbewegung in den Kampfsportarten Karate, Boxen, Syorinji Kenpo.